PENGARUH BAURAN PEMASARAN JASA TERHADAP LOYALITAS KONSUMEN PADA ATRA MART INDERAPURA KECAMATAN PANCUNG SOAL KABUPATEN PESISIR SELATAN - Yengki, Honghayu; Utami, Hayu Yolanda; Arnaldi, Arnaldi (Pendidikan Ekonomi, 2014)
ABSTRACTThis study aims to reveal the influence : products to customer loyalty in Atra Mart Inderapura Kecamatan Pancung Soal Kabupaten Pesisir Selatan ( X1 ) , prices on consumer loyalty in Atra Mart Inderapura Kecamatan Pancung Soal Kabupaten Pesisir Selatan ( X2 ) , the location of the customer loyalty in the Atra Mart Inderapura Kecamatan Pancung Soal Kabupaten Pesisir Selatan ( X3 ) , the promotion of customer loyalty in the District Mart Atra Inderapura Kecamatan Pancung Soal Kabupaten Pesisir Selatan ( X4 ) , the people customer loyalty in the Mart Atra Inderapura Kecamatan Pancung Soal Kabupaten Pesisir Selatan ( X5 ) , the proses loyalty consumers in Atra Mart Inderapura Kecamatan Pancung Soal Kabupaten Pesisir Selatan ( X6 ) , physical evidence on consumer loyalty in Atra Mart Inderapura Kecamatan Pancung Soal Kabupaten Pesisir Selatan ( X7 ), and the marketing mix to customer loyalty in Mart Atra Inderapura Kecamatan Pancung Soal Kabupaten Pesisir Selatan. This type of research conducted in this study is descriptive Associative . The population in this study are all consumers who shop at Atra Mart Inderapura District of South Coastal District Problem beheaded . Technique of sampling is non -probability sampling is purposive sampling technique which amounts to 80 people . Data were collected through a questionnaire using a Likert scale that has been tested validity and reliability . The data analysis technique used is descriptive analysis . To test the hypothesis used t test and f test . Based on the results of t-test of hypothesis testing products and a significant positive effect on consumer loyalty in Atra Mart with a coefficient of 0.167 , t-test positive and significant price effect on consumer loyalty in Atra Mart coefficient value of 0.117 , t test locations and significant positive effect on loyalty Atra Mart consumers on the value of the coefficient of 0.136 , t-test campaign positive and significant effect on customer loyalty tehadap Atra Mart with coefficient of 0.144 , t test person / employee positive and significant effect on customer loyalty tehadap Atra Mart with coefficient of 0.095 , t test process positive and significant effect on customer loyalty tehadap Atra Mart with coefficient of 0.144 , t-test physical evidence tehadap positive and significant effect on customer loyalty Atra Mart with coefficient value of 0.194 . While the f test positive and significant effect between marketing mix to customer loyalty in Atra Mart with a significance level of 0.000 . The magnitude of the effect of marketing mix on consumer loyalty in Atra Mart is 92.8 % and the remaining 7.2 % is influenced by other variables not included in the research model .